The intellectual’s class identity - Miroshnychenko, Dmytro (Filosofska Dumka, 2017)
The aim of the article is considering intellectual’s class identity, especially in the modern world, focusing on the possibilities of its self-identification and making distinctions with similar cultural phenomena. The prerequisites of appearance of sociology of intellectuals are shown and its significant conditionality with the subject of study is marked. The relevance of these problems and the degree of elaboration in the domestic scientific literature are analyzed. The author has indicated three main approaches that stand out in the study of social groups of intellectuals: their consideration as a separate class, as a manifestation of the class of origin and classless approach to them. The article describes the genealogy of each of these approaches and their main representatives in the 20th century. It was suggested a fundamental change in the way of the existence and role of intellectuals in modern society.